Service contracts in state dynamics (2016)
This article seeks to substantiate the main features of the recruitment service fees and analyzed from the perspective of the state, its impact on public management from its implementation with the law 909 of 2004, Act 489 of 1998 and different regulations governing their actions. In the same way the implications for public administration the fact of having more employees for this type of contract that relate plant. Meritocracy, in this context reveals the main focus of work, linking effectively, the conditions and requirements that are regulated by the National Civil Service Commission for employee income administrative career and that once they are approached by an entity or a nominator for the income of employees for services rendered. Finally it is to recognize the benefits of the law, in the conception of the spirit of it and not result in the execution of contractual practices, making the state a slow state, bureaucratized and less effective in the perception of the citizen.